Main group mechanochemistry - Gečiauskaitė, Agota A.; García, Felipe (Beilstein Journal of Organic Chemistry, 2017)
Over the past decade, mechanochemistry has emerged as a powerful methodology in the search for sustainable alternatives to conventional solvent-based synthetic routes. Mechanochemistry has already been successfully applied to the synthesis of active pharmaceutical ingredients (APIs), organic compounds, metal oxides, coordination compounds and organometallic complexes. In the main group arena, examples of synthetic mechanochemical methodologies, whilst still relatively sporadic, are on the rise. This short review provides an overview of recent advances and achievements in this area that further validate mechanochemistry as a credible alternative to solution-based methods for the synthesis of main group compounds and frameworks.
Keywords: ball milling; main group; mechanochemical synthesis; mechanochemistry